2004
DOI: 10.1152/physrev.00046.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role of Caveolae and Caveolins in Health and Disease

Abstract: Although they were discovered more than 50 years ago, caveolae have remained enigmatic plasmalemmal organelles. With their characteristic “flasklike” shape and virtually ubiquitous tissue distribution, these interesting structures have been implicated in a wide range of cellular functions. Similar to clathrin-coated pits, caveolae function as macromolecular vesicular transporters, while their unique lipid composition classifies them as plasma membrane lipid rafts, structures enriched in a variety of signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
800
1
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 801 publications
(821 citation statements)
references
References 280 publications
(315 reference statements)
12
800
1
8
Order By: Relevance
“…For example, the three proteins neph, nephrin and podocin form microdomains in the slit diaphragm of the kidney [62]; prion proteins and other GPI-anchored proteins assemble in reggie/flotillin microdomains [6], and mechanosensory ion channels function within stomatin microdomains [63]. Even unrelated proteins such as caveolins perform comparable scaffolding functions in analogous caveolae DRM structures [64]. Interestingly, caveolins present certain structural similarities to reggies/flotillins, such as palmitoylation sites [65] and oligomers in DRM fractions [66].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the three proteins neph, nephrin and podocin form microdomains in the slit diaphragm of the kidney [62]; prion proteins and other GPI-anchored proteins assemble in reggie/flotillin microdomains [6], and mechanosensory ion channels function within stomatin microdomains [63]. Even unrelated proteins such as caveolins perform comparable scaffolding functions in analogous caveolae DRM structures [64]. Interestingly, caveolins present certain structural similarities to reggies/flotillins, such as palmitoylation sites [65] and oligomers in DRM fractions [66].…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper has shown evidence that GLP-1R may also undergo a caveolin-1-dependent trafficking to and from the cell membrane (Syme et al, 2006). The caveolins are a family of scaffolding proteins encoded by three genes (caveolin-1, 2, and 3) that coat caveolae (Cohen et al, 2004). Caveolae are plasmalemmal organelles, with a high lipid content, that, similar to clathrin-coated pits, function as macromolecular vesicular transporters.…”
Section: Glp-1r In the Pancreasmentioning
confidence: 99%
“…76 This pathway is of considerable interest in particular for molecular conjugates containing pathogen-derived trafficking peptides, since many pathogens (SV40 and cholera toxin included) are thought to use the caveolar pathway to evade degradation in the lysosomes. 77 Using different sized microspheres, Rejman et al 78 showed that molecular size can dictate whether cell entry occurs by clathrin or caveolae-mediated endocytosis. Microspheres of 200 nm in diameter or less entered cells through clathrin-coated pits by a microtubule dependent pathway.…”
Section: Caveolae-mediated Endocytosismentioning
confidence: 99%
“…Another inhibitor of caveolae-mediated uptake, genistein, blocked internalization of 450% of 500 nm microspheres whereas 200 nm microspheres were unaffected. As caveolae are typically sized from 55 to 65 nm, 77 this inhibitory effect of anticaveolar agents on large particle uptake was somewhat surprising.…”
Section: Caveolae-mediated Endocytosismentioning
confidence: 99%